Makna Peminatan Akademik Bagi Peserta Didik Di SMA Negeri 1 Sei Suka Kabupaten Batu Bara - Darmayanti, Nefi; Halimah, Siti; Riza, Muhammad Faisal (RESEARCH AND DEVELOPMENT JOURNAL OF EDUCATION, 2021)
Since the enactment of curriculum 2013 nationally, academic interest determination activities at SMA Negeri 1 Sei Suka, conducted with Placement Test in collaboration with competent professional institutions, and the results are conveyed to all new learners according to their potential in the interest of MIPA, IPS and IBB. However, some students try to move academic interest because the reason is not by their wishes or the influence of parents and friends. Researchers are interested in this case so they want to know what academic interest really means for new students, so it is expected that the case for moving academic interest will not happen again in the future. This research uses qualitative approach with case study techniques where informants are primarily learners who receive test results and students who move academic interest. Data collection is done by interview techniques in person or by phone. Data validation is done by triangulation, namely the results of interviews of learners compared to the interviews of informants supporting the Principal, Vice Principal, Subject Teachers and Parents of learners, as well as the theories of experts, the results of previous research and also supporting documents. The results of this study finally revealed about the preparation of learners before choosing academic interest, consideration of learners choosing the concentration of MIPA, IPS and IBB, as well as how learners interpret academic interest and the reason students move academic interest